The sum of n+1 consecutive squares, beginning with the square of
n(2n+1),
is equal to the sum of the squares of the next n consecutive integers.
n=1 32 + 42 = 52
n=2 102 + 112 + 122 = 132 + 142
.
.
.
Prove that the proposition holds for all integers greater than zero.
Ówell the left hand sum is simply
Ó(n(2n+1)+t)² with t=0 to n
this simplifies to
Ó(n^2(2n+1)^2+2n(2n+1)t+t^2) with t=0 to n
n^2(2n+1)^2(n+1)+n^2(2n+1)(n+1)+n(n+1)(2n+1)/6
[6n^2(2n+1)^2(n+1)+6n^2(2n+1)(n+1)+n(n+1)(2n+1)]/6
n(n+1)(2n+1)(6n(2n+1)+6n+1)/6
n(n+1)(2n+1)(12n^2+12n+1)/6 (1)
now the right hand side is simply
Ó(n(2n+1)+n+t)^2 with t=1 to n
Ó(2n(n+1)+t)^2 with t=1 to n
Ó(4n^2(n+1)^2+4n(n+1)t+t^2) with t=1 to n
4n^3(n+1)^2+2n^2(n+1)^2+n(n+1)(2n+1)/6
[24n^3(n+1)^2+12n^2(n+1)^2+n(n+1)(2n+1)]/6
n(n+1)[24n^2(n+1)+12n(n+1)+2n+1]/6
n(n+1)[24n^3+24n^2+12n^2+12n+2n+1]/6
n(n+1)[24n^3+36n^2+14n+1]/6
n(n+1)(2n+1)(12n^2+12n+1)/6
and this is equal to (1) up above, thus this holds for all n>0
*for reference I've edited a typo I made in the simplification of the first summation, I forgot to add togeather the two 6n's to get 12n^2+12n+1 instead of 12n^2+6n+1*
Edited on September 26, 2008, 3:50 pm
|
Posted by Daniel
on 2008-09-26 12:35:54 |